The Fragile X Mental Retardation Protein Regulates Striatal Medium Spiny Neuron Synapse Density and Dendritic Spine Morphology - Huebschman, Jessica L.; Corona, Kitzia S.; Guo, Yuhong; Smith, Laura N. (Frontiers in Molecular Neuroscience, 2020)
The fragile X mental retardation protein (FMRP), an RNA-binding protein which mediates the transport, stability, and translation of hundreds of brain RNAs, is critically involved in regulating synaptic function. Loss of FMRP, as in fragile X syndrome (FXS), is a leading monogenic cause of autism and results in altered structural and functional synaptic plasticity, widely described in hippocampus and cortex. Though FXS is associated with hyperactivity, impaired social interaction, and the development of repetitive or stereotyped behaviors, all of which are influenced by striatal activity, few studies have investigated the function of FMRP here. Utilizing a cortical striatal co-culture model, we find that striatal medium spiny neurons (MSNs) lacking FMRP fail to make normal increases in PSD95 expression over a short time period and have significant deficits in dendritic spine density and colocalized synaptic puncta at the later time point compared to wildtype (WT) MSNs. Acute expression of wtFMRP plasmid in Fmr1 KO co-cultures results in contrasting outcomes for these measures conducted on MSNs at the more mature time point, reducing spine density across multiple spine types but making no significant changes in colocalized synaptic puncta. FMRP’s KH2 and RGG RNA-binding domains are required for normal elimination of PSD95 and stable spine types in this context, and KH2 is required for normal levels of colocalized puncta. Our data are largely consistent with a role for FMRP and its RNA-binding domains in striatal synapse stabilization on developing MSNs, suggesting distinct regional and/or cell type-specific roles for FMRP in regulating synapse structure.